2022
DOI: 10.3390/ijerph192013620
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Alcohol Abuse and the Desire to Receive Mental Health Counselling Predict Suicidal Thoughts/Thoughts of Self-Harm among Female Residents of Fort McMurray

Abstract: Suicidal ideation and thoughts of self-harm continue to be challenging public health problems. It is presently unknown what the prevalence and correlates of suicidal thoughts and self-harm are in female residents of Fort McMurray, a city that has endured wildfires, flooding, and the COVID-19 pandemic in the last five years. This study aimed to determine the prevalence and correlates of suicidal ideation and thoughts of self-harm among female residents of Fort McMurray. A cross-sectional study using an online s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…In our study, demographic variables, such as age, education, employment, and relationship status, as well as clinical variables, including anxiety, depression, obsessive-compulsive disorder, attention deficit hyperactivity disorder (ADHD), and adverse childhood experiences (ACE), did not independently predict likely GAD or MDD. This finding aligns with another study that did not find independent predictors of suicidal ideation and self-harm among participants [ 49 ]. However, it contradicts a different study suggesting a statistically significant association between anxiety level and participant age [ 8 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, demographic variables, such as age, education, employment, and relationship status, as well as clinical variables, including anxiety, depression, obsessive-compulsive disorder, attention deficit hyperactivity disorder (ADHD), and adverse childhood experiences (ACE), did not independently predict likely GAD or MDD. This finding aligns with another study that did not find independent predictors of suicidal ideation and self-harm among participants [ 49 ]. However, it contradicts a different study suggesting a statistically significant association between anxiety level and participant age [ 8 ].…”
Section: Discussionsupporting
confidence: 92%
“…Desire to receive mental health counseling has been associated with an increased likelihood of other mental health issues. For example, a study reported that individuals who desired to receive mental health counseling were seven times more likely to report suicidal ideation and thoughts of self-harm relative to participants who did not desire counseling [ 49 ]. A cross-sectional study among college students during the COVID-19 pandemic also found that individuals with anxiety and depression symptoms significantly desired more psychological knowledge and interventions [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the female gender, relationships with peers in the year of study slightly reduced anxiety (51%) [67]. On the contrary, some studies have suggested that relationship status does not independently predict mental health issues [5,99]. Other general relationships, such as satisfaction with faculty and peer relationships, still led to a considerably high prevalence of anxiety (66.8%), with dissatisfaction with administration leading to even higher anxiety at 74% [60].…”
Section: Sociodemographic Correlates Of Anxiety and Depression Among ...mentioning
confidence: 94%
“…The impact of these conditions on quality of life is significant. They are associated with decreased productivity, social isolation, and, in severe cases, suicide [4,5]. Among undergraduate health science students, the prevalence of depression and anxiety is exceptionally high, likely due to the demanding academic curriculum, clinical rotations, and personal stressors [6,7].…”
Section: Introductionmentioning
confidence: 99%